Effect of varicocelectomy on sperm functional characteristics and DNA methylation. (19th September 2014) - Tavalaee, M.; Bahreinian, M.; Barekat, F.; Abbasi, H.; Nasr‐Esfahani, M. H.
Summary In individuals with varicocele, DNA is damaged due to high level of oxidative stress, and varicocelectomy can overcome this effect. Damaged DNA is less liable to DNA methylation, and antioxidant therapy appears to have the potential to reduce sperm oxidative stress and DNA damage and thereby maintain DNA methylation, while effect of varicocelectomy on DNA methylation patterns has remained unclear. In the light of these considerations, we aimed to examine the effect of varicocelectomy on sperm DNA methylation and functional characteristics. Fifty‐two men with left‐sided varicocele (grade II &III) were included. Sperm parameters, DNA fragmentation, protamine deficiency, oxidative stress and global DNA methylation were evaluated before and 3 months after surgery. Our data show that sperm concentration, percentages of spermatozoon with abnormal morphology, DNA fragmentation, protamine deficiency and oxidative stress significantly improved after surgery. Percentage of sperm motility, global DNA methylation and intensity of DNA methylation also improved after surgery, although the differences were not significant when compared with before surgery. Categorisation of individuals to subgroups revealed that improvement of DNA methylation appears to take place in oligozoospermic individuals, which are more severely affected by state of varicocele. However, this is a preliminary study, and further studies are required to solidify this conclusion.